O uso de inteligência artificial em processos judiciais no Brasil: limites éticos - Freitas, Tiago Alves Serbeto de (2022)
The present work aims at the theoretical construction of criticism about the possibilities of ethical use of artificial intelligence technologies in the context of judicial processes. Thus, the research problematizes the use of artificial intelligence in the forensic sphere and, therefore, proposes a review of sustained literature on three thematic axes, from which, throughout the text, reaped the premises of the reasoning won in the final considerations. The first thematic axis concerns the economic conjuncture surrounding the advent and use of new technologies, as well as the meaning of these technologies in the context of capitalist production and the possibility of resignification of a given technological innovation. The second thematic axis brings us questions about the (im)possibility of materialization of a human-like cognition in a non-biological substrate. Finally, the third thematic axis, elongation of the previous one, addresses the human cognition itself and some visions about the formation and outsourcing of the will. Thus, the work has the scope to study some aspects of decision-making, in the procedural scope, so that it can be projected to what extent it is possible and ethically appropriate to use artificial intelligence, without compromising human participation in the decision-making process. The research concludes by the possibility of profitable use of algorithmic technologies, within the judiciary, as an auxiliary tool, in activities devoid of procedural decision-making content. On the other hand, by contraindication, in the technical, normative and ethical dimensions, of the use of such technologies as a substitute for human labor